Small Medium Entreprise's in East Java are Going to Digital Economy - Muhafidhah Novie (University of Islam Malang, 2017)
The purpose of this study were 1) to identified the problem of UMKM in implementing 60.000 UMKM domain program, 2) to determine the regional government (East Java) involvement in tackling each issues that comes while implementing 60.000 UMKM domain program, and 3) to classified the priority case in implementing this program. Researcher uses observation, interview, and focus group discussion (FGD) as her research methods. Researcher used 150 East Java UMKM as her sample representative. The results of this study showed that the regional government (East Java) was taking a crucial involvement in educating UMKM to implement this program eventhought they only have limited mentor. Researcher suggested that the government should collaborating with college in achieving their goals.Keyword : UMKM, Online, DomainJudul Asli : UMKM Jawa Timur Menuju Ekonomi Digital Berbasis Online